LAYANAN KONSELING INDIVIDUAL BAGI SISWA YANG MENGALAMI KESULITAN BELAJAR DI SMP NEGERI 3 BANJARBARU - Pertiwi, Ratu Mega; irhamni, irhamni (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2018)
Learning activities at school, we are faced with a number of diverse student characteristics. There are students who can take their learning activities smoothly and successfully without experiencing difficulties, but on the other hand not a few students who actually experience difficulties. For this reason, it is necessary to be interested in conducting a research.This study uses qualitative methods to examine the natural object conditions where the researcher is a key instrument of data source sampling conducted purposively, collection techniques with triangulation, qualitative data analysis is inductive, and the results of qualitative research emphasize the meaning rather than generalization. Qualitative research relies on a natural background holistically, positioning humans as a research tool, conducting data analysis inductively, prioritizing the process rather than the results and the results of research conducted agreed by researchers and research subjects.The results of observation, interviews and documentation, the authors conclude that the BK Teacher at SMP NEGERI 3 Banjarbaru plays an active role in the learning that takes place in school, including BK teachers acting as educators who become role models for students, facilitators whose task is to provide ease of learning, advisors who help in each problems experienced by students. The BK teacher must work together with the subject teacher in order to know and monitor the extent to which students have difficulty learning so that the BK teacher can provide the right solution for each student with different characteristics. Keywords: Individual Counseling, Learning Difficulti